HUWE1 variants cause dominant X-linked intellectual disability: a clinical study of 21 patients. (January 2018) - Moortgat, Stéphanie; Berland, Siren; Aukrust, Ingvild; Maystadt, Isabelle; Baker, Laura; Benoit, Valerie; Caro-Llopis, Alfonso; Cooper, Nicola; Debray, François-Guillaume; Faivre, Laurence; Gardeitchik, Thatjana; Haukanes, Bjørn; et al.
Abstract Whole-gene duplications and missense variants in theHUWE1 gene (NM_031407.6) have been reported in association with intellectual disability (ID). Increased gene dosage has been observed in males with non-syndromic mild to moderate ID with speech delay. Missense variants reported previously appear to be associated with severe ID in males and mild or no ID in obligate carrier females. Here, we report the largest cohort of patients withHUWE1 variants, consisting of 14 females and 7 males, with 15 different missense variants and one splice site variant. Clinical assessment identified common clinical features consisting of moderate to profound ID, delayed or absent speech, short stature with small hands and feet and facial dysmorphism consisting of a broad nasal tip, deep set eyes, epicanthic folds, short palpebral fissures, and a short philtrum. We describe for the first time that females can be severely affected, despite preferential inactivation of the affected X chromosome. Three females with the c.329 G > A p.Arg110Gln variant, present with a phenotype of mild ID, specific facial features, scoliosis and craniosynostosis, as reported previously in a single patient. In these females, the X inactivation pattern appeared skewed in favour of the affected transcript. In summary, HUWE1 missense variants may cause syndromic ID in both males and females.